Prevalence of Edwardsiella tarda in Antarctic wildlife - Leotta, Gerardo Aníbal (2009)
For many years, the Antarctic region has been isolated from human activity. However, there is little data available regarding endemic and exotic diseases. The purpose of this work was to determine the prevalence of Edwardsiella tarda in Antarctic wildlife, including birds, mammals and fish. During the summer of 2000 and 2002 in the Potter Peninsula, and during the summer of 2001 and 2003 in Hope Bay, a total of 1,805 faecal samples from Antarctic animals and 50 infertile eggs of Adelie penguins (Pygoscelis adeliae) were collected in order to isolate E. tarda. The classic Edwardsiella tarda was isolated from 281 (15.1%) of the 1,855 Antarctic wildlife samples. This is the first report of E. tarda isolation from southern giant petrels (Macronectes giganteus), brown skuas (Stercorarius lonnbergi), south polar skuas (Stercorarius maccormicki), kelp gulls (Larus dominicanus), greater sheathbills (Chionis albus), chinstrap penguins (Pygoscelis antarctica), eggs of Adelie penguins and Weddell seals (Leptonychotes weddelli). None of the evaluated animals showed clinical signs of disease. Our results suggest that E. tarda is a common bacterium amongst Antarctic birds and mammals.